Angiotensin Converting Enzyme (ACE) inhibitionactivity by Syzygium polyanthum Wight (Walp.) leaves: mechanism and specificity - Ismail, Azlini; Tuan Anuar, Tuan Ashraf Faiz; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar; Omar, Muhammad Nor; Mustafa Al-Ahmad, Basma Ezzat; Wan Ahmad, Wan Amir Nizam (Pharmacognosy Network Worldwide, 2022)
Introduction: One of the potential antihypertensive mechanisms include angiotensin converting enzyme (ACE) inhibition. So far, there is no in-depth study on the ACE inhibition activity of S. polyanthum, an ethnomedicinal plant used in treating hypertension. Thus, we aimed to study the ACE inhibition activity of S. polyanthum leaves by evaluating its potency, mechanism, and specificity. Methods: S. polyanthum leaves were macerated in a bath-sonicator with either water, methanol, ethyl acetate, and hexane producing aqueous (ASP), methanolic (MSP), ethyl acetate (EASP) and hexane (HSP) extracts. Each extract (100 μg/mL) were initially screened for ACE inhibition activity and then compared with standard drug, captopril (2.06 ng/mL), then the most active extract was further tested at 1 to 1000μg/ml. Inhibition mechanism was studied using zinc chloride and bovine serum albumin (BSA), while inhibition specificity was determined upon screening for α-chymotrypsin and trypsin inhibition activity. Results: ASP at 100 μg/ mL exhibited the highest inhibition activity (69.43 ± 0.60 %) compared to MSP (41.63 ± 0.15 %), EASP (9.62 ± 1.60 %), and HSP (45.40 ± 0.15 %). ASP showed dose-dependent ACE inhibition activity with IC50 of 41 μg/mL. ASP’s ACE inhibition activity was significantly reduced in the presence of BSA, but not upon the presence of zinc chloride. ASP did not significantly inhibit α-chymotrypsin and trypsin. Conclusion: This study showed that the enzyme inhibition activity by S. polyanthum leaves was specific towards ACE. The ACE inhibition possibly occurs via protein precipitation and was non-dependent to the chelation with zinc at ACE active site.